Systematic review of interventions for diabetic foot prevention in older diabetic adults - Delabra-Salinas, María Magdalena (Universidad de Sonora, 2022)
Introduction: The diabetic foot is one of the major complications of diabetes; alterations such as peripheral arterial disease and diabetic neuropathy, which initially manifest with foot injuries, which can progress to ulcers and even amputations and cause mobility and independence limitations in older adults. There are different types of interventions to prevent diabetic foot. Nevertheless, for a researcher, before developing an intervention to prevent diabetic foot in older adults, it is essential to review their quality criteria. Objective: Explore the characteristics of the most effective health interventions for diabetic foot prevention in diabetic older adults. Methodology: Systematic review, following the guidelines of “Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols” to prepare the report. The 8.5b risk of bias tool of Cochrane manual was used in order to assess study quality criteria. The sample was nine of 415 studies (1995-2017) from the Scopus, PubMed and Web of Science databases. Results: Foot care education with the support of materials was the most used and evaluated intervention strategy regarding the care behavior and neuropathy symptoms. Conclusions: The most effective interventions to prevent diabetic foot in diabetic older adults included foot care education and awareness, telephone follow-up, printed material, and foot care materials. According to quality criteria of the studies reviewed, it was not possible to determine which intervention is the best.